2019
DOI: 10.21856/j-pep.2019.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The research was carried out as part of investigation work at the SI «V. Danilevsky Institute for Endocrine Pathology Problems of NAMS of Ukraine» «Development of the methodology for the screening of hormonal-active pitui tary tumors, taking into account their clinical and genetic features» (State registration number: 0117U007186).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(36 reference statements)
0
2
0
3
Order By: Relevance
“…Найчастіше серед клінічної симптоматики в пацієнтів зустрічалися акромегалоїдні риси обличчя, що свідчить про пізнє виявлення захворювання. Пізня діагностика акромегалії погіршує стан здоров'я пацієнта, призводячи до появи низки системних порушень, кількість та тяжкість яких збільшується з пролонгацією латентного періоду [11].…”
Section: матеріал і методиunclassified
“…Найчастіше серед клінічної симптоматики в пацієнтів зустрічалися акромегалоїдні риси обличчя, що свідчить про пізнє виявлення захворювання. Пізня діагностика акромегалії погіршує стан здоров'я пацієнта, призводячи до появи низки системних порушень, кількість та тяжкість яких збільшується з пролонгацією латентного періоду [11].…”
Section: матеріал і методиunclassified
“…Гормонально активні пухлини (аденоми) гіпофіза, клінічними проявами яких є синдром акромегалії, за даними різних авторів, трапляються відносно нечасто і належать до класу орфанних захворювань [1][2][3]. Розвиток пухлини -це складний багатоетапний процес, на який впливають генетичні, епігенетичні фак-тори та чинники довкілля, а також стан центральної нервової системи та мікрооточення пухлини [4][5][6][7].…”
Section: вступunclassified
“…It has been reported that autonomously functioning PAs secreting GH only account for 25% of all autonomously functioning PAs and for 2-17% of all PAs [1,2,3,4,5]. Acromegaly is characterized by pathological and disproportionate growth of bones, soft tissues and internal organs, and various metabolic abnormalities (diabetes mellitus, lipid abnormalities, cholelitiasis, hyperthyroidism, splanchnomegaly, respiratory complications, cardiovascular complications, hypertension, impaired calcium metabolism, and peripheral neuropathy) [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%